Web-STAR: A Visual Web-based IDE for a Story Comprehension System. Issue 2 (14th November 2018) - RODOSTHENOUS, CHRISTOS T.; MICHAEL, LOIZOS
Abstract: We present Web-STAR, an online platform for story understanding built on top of the STAR reasoning engine for STory comprehension through ARgumentation. The platform includes a web-based integrated development environment, integration with the STAR system, and a web service infrastructure to support integration with other systems that rely on story understanding functionality to complete their tasks. The platform also delivers a number of "social" features, including a community repository for public story sharing with a built-in commenting system, and tools for collaborative story editing that can be used for team development projects and for educational purposes.